Determination of Fabric Surface Resistance by Van Der Pauw Method in Case of Contacts Distant from the Sample Edge - Tokarska, Magdalena (Wydawnictwo Politechniki Łódzkiej. Wydział Technologii Materiałowych i Wzornictwa Tekstyliów, 2014)
The van der Pauw method can be used to determine the electroconductive properties of textile materials. However, the sample surface resistance can be determined provided that the sample has characteristics typical for the van der Pauw structure. In the paper, a method of evaluating the sample structure is shown. The selected electroconductive woven fabrics are used as an example of van der Pauw structure. An analysis of impact of electrodes placement on the resistance measurements was conducted. Knowing how the resistance of the sample varies with the electrodes distance from the edge, the samples’ surface resistances were calculated in cases when the electrodes are placed at the sample edge. An uncertainty analysis of the samples’ surface resistances was conducted based on the Monte Carlo method.
Keywords: electroconductive properties; woven fabric; van der Pauw structure; van der Pauw method; surface resistance; electrodes placement; Monte Carlo method